Characterizing the gene mutations associated with resistance to gatifloxacin in Mycobacterium tuberculosis through whole-genome sequencing. (November 2021) - Bi, Jing; Guo, Qinglong; Fu, Xiangdong; Liang, Juan; Zeng, Lidong; Ou, Min; Zhang, Juanjuan; Wang, Zhaoqin; Sun, Yicheng; Liu, Lei; Zhang, Guoliang
Highlights: Mutations conferring resistance to gatifloxacin (GAT) remain inadequately characterized. 123 GAT-resistant mutants were isolated and subjected to whole-genome sequencing. Sixty-eight of 123 mutants had gyrA gene mutations (G280A, A281G, G280T and G262T). The remaining mutants harboured gyrB gene mutations (A1495G, C1497A, C1497G and A1503C). Mutations in the gyrA and gyrB genes are the main mechanisms of resistance to GAT. ABSTRACT: Objectives: Gatifloxacin (GAT), a fourth-generation fluoroquinolone (FQ), is used to treat drug-resistant tuberculosis. Although DNA gyrase mutations are the leading cause of FQ resistance, mutations conferring resistance to GAT remain inadequately characterized. Methods: GAT-resistant mutants were selected from 7H10 agar plates containing 0.5 mg/L GAT (critical concentration). Mutations involved in GAT resistance were identified through whole-genome sequencing. Results: In total, 123 isolates demonstrated resistance to GAT. Among these isolates, 55.3% (68/123) had gyrA gene mutations [G280A (D94N), A281G (D94G), G280T (D94Y) and G262T (G88C)]. The remainder (44.7%, 55/123) harboured gyrB gene mutations [A1495G (N499D), C1497A (N499K), C1497G (N499K) and A1503C (E501D)]. Conclusions: Mutations in the gyrA and gyrB genes are the main mechanisms of GAT resistance. These findings provide new insight into GAT resistance, and contribute to molecular diagnosis of GAT resistance in the clinical setting.